2021
DOI: 10.4047/jap.2021.13.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microhardness and wear resistance of dental alloys against monolithic zirconia

Abstract: PURPOSE The aim of this study is to compare the hardness according to the conditions of metal alloys. Moreover, the correlation between the cast crown hardness before and after wear testing and the degree of wear for each dental alloy was assessed. MATERIALS AND METHODS Cast crowns of three metal alloys (Co-Cr, gold, and Ni-Cr alloys) opposing smooth-surface monolithic zirconia were used. The Vickers microhardness of the ingot (which did not undergo wear testing) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…According to reports, a prosthesis's hardness can differ based on the fabrication process it uses, including milling, 3D printing, casting (which can vary depending on the mold used even when using the same casting procedure), and the rate at which the prosthesis cools down after casting. It has been shown that, as grain size increases during the alloy casting process, mechanical strength and surface hardness decrease, even though changes in grain size are independent to changes in yield strength and hardness in the case of gold alloys [32,33]. This study's findings showed that, for both alloys, the hardness of the cast crown was much lower than the ingot's (see Table 6).…”
Section: Microhardnessmentioning
confidence: 62%
“…According to reports, a prosthesis's hardness can differ based on the fabrication process it uses, including milling, 3D printing, casting (which can vary depending on the mold used even when using the same casting procedure), and the rate at which the prosthesis cools down after casting. It has been shown that, as grain size increases during the alloy casting process, mechanical strength and surface hardness decrease, even though changes in grain size are independent to changes in yield strength and hardness in the case of gold alloys [32,33]. This study's findings showed that, for both alloys, the hardness of the cast crown was much lower than the ingot's (see Table 6).…”
Section: Microhardnessmentioning
confidence: 62%
“…These complications were associated with the failures of MZCs and survival rates. However, it is noteworthy that a large number of reports have evaluated the wear of opposing antagonist teeth [17][18][19][20][21][22][23]. This concern was raised from the hardness of MZC.…”
Section: Introductionmentioning
confidence: 99%